MENINGKATKAN KEMAMPUAN BERPIKIR KREATIFMATEMATIK SISWA KELAS VSDN JATIRAHAYU VI DENGAN METODE KOOPERATIF TIPE STAD - Nur Asyiah, Siti (Jurnal Pendidikan Dasar, 2017)
Abstrack: This research aims at improving the students’ creative thinking skill in mathematicsteaching learning using STAD type of cooperative method in the fifth grade of Jatirahayu VI PublicElementary School PondokMelatiBekasi. The two research questions of this research are (1) how canusing STAD type of cooperative improve students’ creative thinking skill in mathematics teachinglearning? and (2) can STAD type of cooperative method improve creative thinking skill?.This studyemploysKemis and Taggar model of action research consisting of plan, action, observation, andreflection.The research results demonstrate that: (1) the students’ creative thinking skill is able to beimproved using STAD type of cooperative method by executing entire steps of that method, and (2)the students’ creative thinking skill improvement is indicated with the increase of average score,scores, creativity level, and the completeness of teaching learning in the cycles I and II.It isrecommended for the teacher and the students to master and apply every step of the method, for theheadmaster to provide the necessary facility that is needed by the teacher, and for the schoolsupervisor to organize and give the proper training and education about the STAD type of cooperativemethod entirely. Key Words: creative thinking, STAD cooperative method